Escaping Sets of Hyperbolic Semigroups - Subedi, Bishnu Hari; Singh, Ajaya (The Nepali Mathematical Sciences Report, 2018)
In this paper, we mainly study hyperbolic semigroups from which we get non-empty escaping sets and Eremenko’s conjecture remains valid. We prove that if each generator of bounded type transcendental semigroups is hyperbolic, then the semigroups are themselves hyperbolic and all components of escaping sets are unbounded.